The Effect of Positional release Therapy Versus Passive Stretching in upper Trapezitis among Dentists – A comparative study - CHUKWUEMEKA SUCCESS OLUEBUBE; DR SENTHIL KUMAR (International Journal of Pharma and Bio Sciences, 2018)
Trapezitis is one of the most frequently occurring condition seen among dentists due to frequent use of the upper extremity and various positions adopted during working hours and the limitation in the oral cavity. This pain can be attributed to numerous risk factors which includes prolonged static postures, repetitive movements, poor positioning, mental stress, physical conditioning and age.3 Various investigators have pointed out the common postural faults among dentists are excessive bending and twisting of the neck and elevation of shoulders. To compare the effect of positional release therapy versus passive stretching in upper trapezitis among dentists. Total of 60 subjects was recruited for study on the basis of inclusion and exclusion criteria after signing the informed consent form.Subjects were divided into two groups(A=PRT and B=PS). The effect of positional release therapy versus passive stretching was compared in dentists with sample size of 60.Visual analogue scale was used to quantify the pain threshold before the treatment and after the treatment. After 8 weeks of intervention there was considerable improvement and significant difference among in pain reduction between those who received positional release therapy than those that received passive stretching. The post-test mean value of VAS in Group-A is 3.30 (SD 0.95) and post-test mean value of Visual analog scale (VAS) in Group-B is 6.70 (SD 1.04). This shows that Group-A is lesser than Group-B with the P value (0.001). The present study concluded that both the technique is effective in reducing pain in subjects with upper trapezitis but positional release therapy is significantly more effective than Passive Stretching in reducing pain intensity for subjects with upper trapezitis.